2013
DOI: 10.5901/ajis.2013.v2n12p101
|View full text |Cite
|
Sign up to set email alerts
|

Acid Rain and Environmental Problems: Implications for the Teaching of Biology in Schools in Riverine Communities

Abstract: This study was conducted to investigate the influence of acid rain and environmental problems on the teaching of Biology in schools in the riverine communities of Akwa Ibom State -Nigeria. One hundred and eighty (180) Biology teachers were selected using the stratified sampling technique. A questionnaire titled "Acid rain and Teaching of Senior Secondary Biology" (ARTSSB) was used to collect data for testing the four null hypotheses of the study at .05 level of significance. Data analysis was done using the t-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…It also decreases the growth of forest trees (Osu and Expo 2013). A number of studies have shown that acid rains have serious effects on vegetative organ and generative structure [3,4]. Acid rain induces changes in cellular biochemistry and whole plant physiology.…”
Section: Introductionmentioning
confidence: 99%
“…It also decreases the growth of forest trees (Osu and Expo 2013). A number of studies have shown that acid rains have serious effects on vegetative organ and generative structure [3,4]. Acid rain induces changes in cellular biochemistry and whole plant physiology.…”
Section: Introductionmentioning
confidence: 99%